Solve for \( u \) in the equation \( 4u^{2} + 3 = -8u \).
Rearranging the equation.
We start with the equation \( 4u^{2} + 3 = -8u \). Moving all terms to one side gives us \( 4u^{2} + 8u + 3 = 0 \).
Factoring the polynomial.
The polynomial \( 4u^{2} + 8u + 3 \) can be factorized as \( (2u + 1)(2u + 3) \).
Finding the solutions.
Setting each factor to zero, we solve \( 2u + 1 = 0 \) and \( 2u + 3 = 0 \), yielding the solutions \( u = -\frac{1}{2} \) and \( u = -\frac{3}{2} \).
The solutions for \( u \) are \( u = -\frac{3}{2}, -\frac{1}{2} \).
The solutions for \( u \) are \( \boxed{-\frac{3}{2}, -\frac{1}{2}} \).
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.